Numerical analysis of MHD free convection boundary layer flow of heat and mass transfer in case of air and water - Ali, M; Alam, MS; Alim, MA (Bangladesh Journal of Scientific and Industrial Research, 2016)
The present work has been studied the effect of various parameters on MHD boundary layer flow of heat and mass transfer in case of air and water. The governing partial differential equations are transformed to higher order ordinary differential equations by using similarity transform. This coupled ordinary differential equations are performed by shooting iteration technique along with Runge-Kutta integration scheme. The effects of various parameters on velocity, temperature and concentration profiles are discussed numerically and shown graphically. Therefore, the results of velocity field decreases for increasing values of magnetic parameter and chemical reaction parameter in case air and salt water but increases for Grashof number and modified Grashof number. The temperature field decreases in the presence of magnetic parameter but significant increasing effect for chemical reaction parameter, Grashof number and modified Grashof number in case of air and salt water. Also, the concentration profile is slightly increased for increasing the values of magnetic parameter and slightly decreased for Grashof number and modified Grashof number but significant decreasing effect are observed for reaction parameter. Finally, the numerical values of the shear stress, rate of temperature and rate of concentration are also shown in a tabular form Bangladesh J. Sci. Ind. Res. 51(2), 139-146, 2016